(untitled) (American Innovator: Journal of Emerging Technologies and Research, 2026)
Writing is widely regarded as one of the most challenging components of the International English Language Testing System (IELTS) examination. Many candidates struggle to produce coherent, welldeveloped essays within the limited time available during the test. Traditional approaches to IELTS writing instruction often emphasize the final product rather than the writing process itself. However, contemporary educational research suggests that the Process Writing Approach can significantly improve learners’ writing competence by focusing on planning, drafting, revising, editing, and reflection. This article examines the application of the Process Writing Approach to IELTS Writing Task 2 preparation, discusses its theoretical foundations, and explores its potential to enhance writing quality, learner autonomy, and examination performance